Cyberbullying, schools and the law: A comparative study in Northern Ireland and the Republic of Ireland - MCGUCKIN, CONOR (My University, 2015)
Background This study addresses the fast developing behavioural issue of cyberbullying in schools and its complex legal context. Purpose This study set out to investigate teachers’ perceptions of the extent of cyberbullying and the extent to which school leaders in Northern Ireland and the Republic of Ireland feel knowledgeable and confident about dealing with cyberbullying problems in school. The study also examined the legal responsibility that schools in Northern Ireland and the Republic of Ireland have in dealing with incidents of cyberbullying. Sample The sample comprised 14 headteachers and senior teachers from primary and post-primary schools (focus groups), and a further 143 school headteachers in Northern Ireland and the Republic of Ireland who responded to the postal questionnaire. Design and Methods The sample was stratified according to geographical location, school management type and school size. The study had qualitative and quantitative elements. Focus group discussions were held in Northern Ireland and the Republic of Ireland, involving experienced primary and post-primary teachers and headteachers. Questionnaires were sent to primary and post-primary school headteachers (n=143 completed: response rate = 28.6%). Data were analysed to provide a descriptive overview of knowledge and attitudes as well as the experiences of staff working in schools in both jurisdictions. Results The study indicates that school leaders in both Northern Ireland and the Republic of Ireland reported a level of frustration in their attempts to deal with the growing and very complex problem of cyberbullying. They expressed a desire for more guidance from their respective government departments of education. Analysis of data suggests that confusion surrounding the legal responsibilities of schools was common in both jurisdictions. Findings indicate that rather than relying on evidence-based strategies and procedures proposed by government, school leaders were resorting to ad hoc solutions, at best consulting neighbouring schools, while trying to unravel intricate webs of interpersonal online aggressive acts, many of which had taken place outside of school and outside of school hours. Conclusion Recommendations are made in relation to the development and dissemination of training and resources for schools in both jurisdictions. In describing the challenges faced by school leaders in dealing with cyberbullying, this study highlights, more generally, the need for the development of guidance and professional support frameworks to help educators manage the problems that are presented by this complex and evolving social phenomenon. Schools,
PUBLISHED
Keywords: Cyberbullying; Law; Teachers